1997
DOI: 10.1016/s0167-2789(97)00022-5
|View full text |Cite
|
Sign up to set email alerts
|

Scalar transport in compressible flow

Abstract: Transport of scalar fields in compressible flow is investigated. The effective equations governing the transport at scales large compared to those of the advecting flow are derived by using multi-scale techniques. Ballistic transport generally takes place when both the solenoidal and the potential components of the velocity do not vanish, despite of the fact that it has zero average value. The calculation of the effective ballistic velocity $V_b$ is reduced to the solution of one auxiliary equation. An analyti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 26 publications
2
60
0
Order By: Relevance
“…The effective diffusion coefficient is determined by the traveling potential. Similar effects are known in the context of homogenization theory, see e.g., [5,6]. The stochastic Stokes' drift has the additional difficulty that it is an evolution problem in which the small parameter and the time are not independent.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…The effective diffusion coefficient is determined by the traveling potential. Similar effects are known in the context of homogenization theory, see e.g., [5,6]. The stochastic Stokes' drift has the additional difficulty that it is an evolution problem in which the small parameter and the time are not independent.…”
Section: Introductionmentioning
confidence: 61%
“…Using relative entropies and homogenized logarithmic Sobolev inequalities, one can then prove (5). The function u ∞ therefore describes the asymptotic regime of u, in self-similar, traveling variables.…”
Section: The Diffusive Traveling Frontmentioning
confidence: 98%
See 1 more Smart Citation
“…Making use of this solution, Vergassola and Avellaneda 14 showed that static potential flows cannot produce any heterogeneity induced large scale drift components, and that the large scale drift equals the local drift value. The assumption of a vanishing mean drift is crucial for this statement to hold.…”
Section: ͑54͒mentioning
confidence: 99%
“…In this limit the goal is to derive the expression of the asymptotic diffusion coefficient renormalized by the presence of the small scale velocity field. This can be accomplished exploiting asymptotic methods (see, e.g., [6,8,9,10,11,12,13,14] among the others). However, in many physical circumstances one has that the velocity field may be though as a smallscale advecting velocity field (at scale ℓ) superimposed to a large-scale, slowly varying component (at scale L ≫ ℓ).…”
Section: Introductionmentioning
confidence: 99%